HARMONISASI KOMUNIKASI INTERPERSONAL KELUARGA DI DAERAH MINORITAS KABUPATEN KARO (STUDI KASUS PADA KELUARGA USIA PERKAWINAN 5, 10 DAN 15 TAHUN) - sari, etika; Sari Atika Parinduri; Risydah Fadhilah (AT-TAWASUL, 2025)
This research focuses on harmonization of interpersonal communication in minority families in Karo Regency. The aim of this research aims to find out how families from minority areas maintain harmony in their households, looking at the interpersonal communication at home between partners and children. As for other things, does the age of the household also have an impact on the harmony of a happy family? This research is field in nature where the object of the research is observation and in-depth interviews in the Muslim minority area, namely Karo district, with 20 families as informants. The results show that the interpersonal communication of minority couples in the Karo district is naturalistic, the partners are committed to each other both in terms of religion, relationships, parenting styles towards children and taking care of each other's weaknesses/strengths. As for the length of marriage, the age of marriage plays a very important role, apart from being faithful to each other, providing mutual support to one's partner is the key to household harmonization in this research. The shared parenting pattern shows evidence that to create a generation that has good moral character, of course it is the duty of a father and mother according to their function.